Case fatality rate for Ebola disease, 1976-2022: A meta-analysis of global data - Jonathan Izudi; Francis Bajunirwe (Elsevier, 2024)
An up-to-date pooled case fatality rate (CFR) for Ebola disease (EBOD) at the global level is lacking. We abstracted EBOD data from 1976 to 2022 for 16 countries and 42 outbreaks to conduct a meta-analysis. The pooled CFR was 60.6% (95% confidence interval (CI) 51.6-69.4; 95% prediction interval 12.9-99.1). Of the four ebolaviruses, Zaire virus was the most lethal (CFR = 66.6%, 95% CI 55.9-76.8), then Sudan virus (CFR=48.5%, 95% CI 38.6-58.4), Bundibugyo virus (CFR=32.8%, 95% CI 25.8-40.2) and Tai Forest virus (CFR= 0%, 95% CI 0.0-97.5). The CFR in sub-Saharan Africa was 61.3% (95% CI 52.8-69.6) and for the rest of the world was 24.5% (95% CI 0.0-67.9%). CFR declined over time but stabilized at 61.0% (95% CI, 52.0-69.0) between 2014 and 2022. Overall, the EBOD CFR is still high and heterogeneous. Accordingly, early diagnosis, early treatment if available, and supportive care are important to prevent significant morbidity and mortality.